THE USE OF FLASHCARDS FOR TEACHING WRITING TO ENGLISH YOUNG LEARNERS (EYL) - Paramita Kusumawardhani (Scope : Journal of English Language Teaching, 2020)
The aims of this research are to know about the use of flashcards to improve the English Young Learners’ writing skills. English has four skills to be learned; they are listening, speaking, reading, and writing, and writing skill is the most difficult skill to be taught and learnt. Flashcards are one of the ways to improve the learners’ skill, especially EYL writing skill. The participants of this research are English Young Learners (EYL) in of the English Course at Gading Serpong, Tangerang. Classroom Action Research (CAR) was used as the method of the research and the English Young Learners’ (EYL) story paper are used as the instruments of the research. The results of the research are: (1) Most learners were excited when they are asked to see the colorful flashcard; (2) Learners who have good writing skill could make the story by completing the missing words and answer the questions then arrange the answer sentences well and (3) Learners who are not really master in writing, got some difficulties not only in completing the missing words but also answering then arranging the answer sentences well.